2014
DOI: 10.2478/ppb-2014-0028
|View full text |Cite
|
Sign up to set email alerts
|

Emotion understanding, interpersonal competencies and loneliness among students

Abstract: The study examines the associations of emotion understanding, interpersonal competencies, loneliness and correlated variables (perceived social support, quality of social networks). Two conceptual models of relations were tested. In the first model it was hypothesized that interpersonal competencies mediate relations between emotion understanding and loneliness, perceived social support and quality of social networks. In the second model emotion understanding was tested as a moderator of relationships between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 93 publications
(125 reference statements)
0
1
0
Order By: Relevance
“…Financial difficulties, academic difficulties, sickness, and maladjustment have been found to be the major reasons for dropping out of university (31). It has been found that maladjustment in students is related to difficulties in the transition from high school to university (32, 33), that moving to a new city and away from the family environment is stressful (34), and that the varying and superficial relationships promote loneliness (35). Early prevention, such as providing advice, information, financial support, or companionship during the first year of college, may be helpful (34).…”
Section: Discussionmentioning
confidence: 99%
“…Financial difficulties, academic difficulties, sickness, and maladjustment have been found to be the major reasons for dropping out of university (31). It has been found that maladjustment in students is related to difficulties in the transition from high school to university (32, 33), that moving to a new city and away from the family environment is stressful (34), and that the varying and superficial relationships promote loneliness (35). Early prevention, such as providing advice, information, financial support, or companionship during the first year of college, may be helpful (34).…”
Section: Discussionmentioning
confidence: 99%